Preparation and characterization of foamed glass-ceramics based on waste glass and slow-cooled high-titanium blast furnace slag using borax as a flux agent - Zhou, Hongling; Feng, Keqin; Liu, Yanfang; Cai, Liangping (Journal of non-crystalline solids, 2022)
•Foamed glass-ceramics were prepared at 1000 °C through the one-step sintering process.•The one-step sintering process concurrently completed foaming and crystallizing process.•Borax was influential to both foaming and crystallizing process of foamed glass-ceramics. Foamed glass-ceramics were prepared at 1000 °C through the one-step sintering process by applying waste glass and slow-cooled high-titanium blast furnace slag as raw materials. This study investigated the effects of borax as the flux agent on the crystalline phases, microstructure, and properties of foamed glass-ceramics, respectively. It was found that the borax would decrease the system's softening temperature and viscosity, thus enhancing the foaming and crystallizing process. Besides, the XRD results showed that the main crystal types of foamed glass-ceramics presented no difference with different contents of borax addition, but their crystallinity and crystal morphology differed. With the increasing borax content, the porosity and water absorption increased, while the volume density, thermal conductivity, and compressive strength all decreased. In particular, the sample added with 6 wt% borax exhibited the optimal comprehensive properties. This study provided a practical guideline for effectively reusing solid industrial wastes to produce foamed glass-ceramics.